Geoecologic description of the license area «Lagansky» - S. K. Monakhov; O. I. Esina (Юг России: экология, развитие, 2015)
The article presents a geoecologic description of the license area “Lagansky”, located in the north-western part of the Caspian Sea, comprising a brief description of natural conditions and anthropogenic load on its water area. The article provides the reader with up-to-date data on marine environment pollution at the license area “Lagansky”.